2002
DOI: 10.2320/matertrans.43.406
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Microwave Absorption Properties of Polymer-Protected Cobalt Nanoparticles

Abstract: This paper describes magnetic properties and microwave absorption properties of polymer-protected cobalt nanoparticles. Cobalt nanoparticles were prepared using the thermal decomposition of dicobalt octacarbonyl in ethylene glycol. They were stabilized and dispersed by coexisting with poly(N -vinyl-2-pyrrolidone) (PVP), resulting in an average diameter of 45 nm. The X-ray diffraction (XRD) analysis revealed that the Co-PVP sample synthesized at 170 • C for 3 h, with the mole ratio of cobalt : PVP = 1 : 10 (mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…To overcome this shortcoming, an effective approach is to disperse magnetic metallic particles with size less than the skin depth in insulator matrix. Various material systems (e.g., ␣-Fe/Fe 3 B/Y 2 O 3 [3], Fe/SiO 2 [4], Co/SiO 2 [5], Co/PVP [6], Co x Ni (100−x) /MnO 2 [7,8], Ni/C [9]) have been attempted. The electrical resistivity of these systems can be enhanced by several orders and reach 10 4 cm [3]; and the eddy current effect can be suppressed effectively due to the presence of the insulator matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this shortcoming, an effective approach is to disperse magnetic metallic particles with size less than the skin depth in insulator matrix. Various material systems (e.g., ␣-Fe/Fe 3 B/Y 2 O 3 [3], Fe/SiO 2 [4], Co/SiO 2 [5], Co/PVP [6], Co x Ni (100−x) /MnO 2 [7,8], Ni/C [9]) have been attempted. The electrical resistivity of these systems can be enhanced by several orders and reach 10 4 cm [3]; and the eddy current effect can be suppressed effectively due to the presence of the insulator matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Co nanochains can reach reflection loss peak about −11 dB at 17.2 GHz at the thickness of 2.5 mm, and Co nanoparticles can only reach the maximum reflection loss −5 dB in 2–5 GHz at the thickness of 3.16 mm [4], [5]. While chain-like Co flower at a thinner thickness of 2 mm as shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…However, as a kind of representative magnetic material, only a few literatures have discussed the microwave absorption property of Co due to its poor microwave absorption ability. Kato et al has validated cobalt particles could only exhibit strong microwave absorption during very narrow frequency band [4], while Cao et al found hollow chain-like cobalt displayed absorption ability no stronger than −11 dB [5]. Therefore, it is valuable to deeply explore the microwave absorption mechanism of Co and find the route to improve its absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability of Co 2 (CO) 8 /polyvinyl-2-pyrrolidone (PVP) composite of 5 vol.% was 4.3, 10 vol.% 5.8, and 50 vol.% only 1.7 at 1 GHz. 26 The cobalt inks exhibited (in Fig. 5) a relative real permeability of 1.3-1.5 (45 MHz).…”
Section: Microwave Characterisationmentioning
confidence: 99%